2021
DOI: 10.3390/ani11061531
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Studies of Somatic Cell Count in the Assaf Breed

Abstract: A genome-wide association study (GWAS) was performed to identify new single nucleotide polymorphisms (SNPs) and genes associated with mastitis resistance in Assaf sheep by using the Illumina Ovine Infinium® HD SNP BeadChip (680K). In total, 6173 records from 1894 multiparous Assaf ewes with at least three test day records and aged between 2 and 7 years old were used to estimate a corrected phenotype for somatic cell score (SCS). Then, 192 ewes were selected from the top (n = 96) and bottom (n = 96) tails of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…For example, significant associations with body weight, growth-related and body conformation traits were identified by GWAS in 150 Dazu Black goats [ 18 ], in 95 Sudanese goats [ 28 ], in 69 Egyptian Barki sheep [ 33 ], and in 96 Baluchi sheep [ 34 ]. Genome-wide associations with other economic important traits were found in sample sizes of 192 animals [ 35 , 36 ]. In this regard, we believe that it possible to use a sample of 269 animals for our research.…”
Section: Discussionmentioning
confidence: 99%
“…For example, significant associations with body weight, growth-related and body conformation traits were identified by GWAS in 150 Dazu Black goats [ 18 ], in 95 Sudanese goats [ 28 ], in 69 Egyptian Barki sheep [ 33 ], and in 96 Baluchi sheep [ 34 ]. Genome-wide associations with other economic important traits were found in sample sizes of 192 animals [ 35 , 36 ]. In this regard, we believe that it possible to use a sample of 269 animals for our research.…”
Section: Discussionmentioning
confidence: 99%
“…Öner et al [48] reported the development of GWASs in Assaf sheep using animals with extreme values (the highest 10% and the lowest 14% values) of somatic cell count, and the validation of the results using all the analyzed animals. Li et al [49] reported the development of GWASs in beef cattle using all the animals and GWASs using animals with extreme values (different combinations of high and low percentiles) of yearling weight.…”
Section: Methods 1 Linear Modelmentioning
confidence: 99%
“…Mastitis is the most common inflammatory condition that develops as a result of infection with pathogenic microorganisms or physical trauma. The expense of lost milk, as well as diminished milk output and quality, are all related to significant economic losses for the dairy sheep industry [2]. Somatic cell count (SCC) or log transformed SCC (somatic cell score, SCS) has relatively higher heritability compared to mastitis (from 0.14 to 0.19 for SCS and from 0.02 to 0.05 for mastitis) and are used as the first trait to improve mastitis resistance [3].…”
Section: Introductionmentioning
confidence: 99%